Rosuvastatin Therapy in Prevention of Contrast-Induced Acute Kidney Injury in Patients with Chronic Kidney Disease - Asadullah, Bhagwan Das, Santosh Kumar, Abdul Manan Junejo, Rafia Memon, Om Lal, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the efficacy of rosuvastatin therapy in prevention of contrast-induced acute kidney injury in patients with chronic kidney disease. Study design: Descriptive cross-sectional study. Place and Duration of Study: Department of Nephrology, Jinnah Postgraduate Medical Centre (JPMC), Karachi, Pakistan from 21st January 2020 to 20th July 2019. Methodology: One hundred and twenty-five patients were enrolled. Blood samples and creatinine levels were taken to measure CIN at 48 h and 72 h after PCI to assess the efficacy of therapy. Results: The mean age was 51.1±10.6 years and mean duration of chronic kidney disease was 6.7±3.6 months. Seventy-eight (62.4%) were males while 47 (37.6%) were females. Efficacy of rosuvastatin therapy was found in 97 (77.6%) patients. Conclusion: The efficacy of rosuvastatin therapy is an effective and safe treatment option in prevention of contrast induced acute kidney injury in patients with chronic renal failure. Keywords: Efficacy, Rosuvastatin, Contrast induced nephropathy (CIN), Acute kidney injury, Chronic kidney disease